Permohonan Sita Marital Harta Bersama dalam Perkara Perceraian Analisis Putusan Perkara Nomor 411/Pdt/2020/PT.DKI Jo.No.727/Pdt.G/2016/PN.Jkt.Brt - Vindy Puri Amaliyani; Muhammad Ali Hanafiah Selian (Universitas Batanghari Jambi, 2022)
Every marriage is expected to be an eternal and happy family, but in fact, many households end up in divorce. Divorce often creates a new problem related to the distribution of joint property. Therefore, the law has regulated the protection of the joint property by applying for Marital confiscation as a form of guarantee in terms of obtaining its share at the time of the Distribution of Joint Assets later. The purpose of this study was to determine how the application of marital confiscation of joint property in divorce. To answer these problems, a research was carried out through a normative approach and using library data collection methods and interviews. The results of this study are the basis or reason for the rejection of Marital confiscation in the case studied is the judge's consideration which states that the application for distribution of joint assets cannot be combined with the lawsuit for divorce. In fact, in this case, the petition for the distribution of joint assets was not requested at all, but in the petitum, only the marital confiscation was requested. The impact of the rejection of this marital confiscation is that the joint property can be transferred to a third party without the knowledge of the other litigants.